Fatigue Crack Growth and Fracture of 30 wt% B4C/6061Al Composites. Issue 9 (30th January 2017) - Li, Y. L.; Wang, W. X.; Zhou, J.; Chen, H. S.; Zhao, J. C.; Wang, B. D.
Abstract: This paper focuses on studying the fatigue crack growth (FCG) characteristics and fracture behaviours of 30 wt% B4 C/6061Al composites fabricated by using powder metallurgy and hot extrusion method. Compact tension (CT) specimens having incisions parallel to the extrusion direction (T‐D) and perpendicular to the extrusion direction (E‐D) were investigated through FCG tests. Results show that, at low/medium stress‐intensity factor range levels (Δ K  ≤ 9), crack propagation rate in E‐D specimens is lower than that in T‐D specimens because the elongated B4 C particles parallel to the extrusion direction in E‐D specimens can deflect the crack. The scanning electron microscope micrographs of the fractured surface illustrate that crack mainly propagates in the matrix alloy at the initial stage of its propagation and propagates more remarkably near the particle‐matrix interface with the increase of ΔK value. B4 C particles are also found to be easy to fracture during the rapid crack propagation. Based on fracture analyses, considering the impacts of factors like crack deviation, plastic zone size at the crack tip, and crack driving force, a 2‐D crack propagation model was developed to study the fatigue crack propagation mechanism in the 30 wt% B4 C/6061Al composite.